Marketing Strategy through Swot Analysis on the Puncak Mas Tourist Attraction in Bandar Lampung - Niken Paramitasari; Yan Aditiya Pratama; Andri Winata; Aditya Mandala Putra (Prosiding International conference on Information Technology and Business (ICITB), 2021)
The tourism sector in Indonesia is currently considered to have an effective role in increasing the country's foreign exchange. The Covid-19 pandemic has an impact ontourism sector activities and recorded losses of up to IDR 10 trillion during the implementation of the Large-scale social restrictions or LSSR (Indonesian: Pembatasan Sosial Berskala Besar or PSBB). The 2020 report states that the number of tourists has decreased by 75% compared to 2019. In this study, data was obtained through distributing questionnaires to visitors in Puncak Mas tourist attraction. It was processed using a SWOT analysis technique. The result of this study showed that Puncak Mas tourist attraction had strength in Internal Factors and there were various threats of quite inhibiting. Diversification must be carried out so that there was development in tourist areas and tourism renewal that provides innovation, security, and comfort for Puncak Mas tourist attraction.Keywords— Marketing Strategy, SWOT, Tourism